Emergent clusteroluminescence from nonemissive molecules - Jianyu Zhang; Zuping Xiong; Haoke Zhang; Ben Zhong Tang (Nature Communications)
Abstract Once considered the exclusive property of conjugated molecules, efficient and visible-light luminescence from non-conjugated and nonemissive molecules in the clustered state, known as clusteroluminescence (CL), has attracted much attention recently due to its special photophysical behaviors and behind electronic interactions. This perspective discusses the development of the CL phenomenon, followed by the typical photophysical features, examples, mechanisms, and potential applications of CL materials, to provide a comprehensive picture of this emerging field. Starting with organic clusters, inorganic, metallic, and hybrid clusters with CL properties are also introduced, and the perspective shift from covalent interactions at the molecular level to non-covalent interactions at the aggregate level is invoked.